2005
DOI: 10.1002/polb.20369
|View full text |Cite
|
Sign up to set email alerts
|

Molecular orientation behavior of poly(vinyl chloride) as influenced by the nanoparticles and plasticizer during uniaxial film stretching in the rubbery stage

Abstract: The structural evolution during uniaxial stretching of poly(vinyl chloride) films was studied using our real time spectral birefringence stretching machine. The effect of clay loading and the amount of plasticizer as well as the rate effects on the birefringence development and true mechanical response are presented with a final model summarizing the molecular phenomena during stretching. Mechano-optical studies revealed that birefringence correlated with mechanical response (stress, strain, work) nonlinearly.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Consequently, the mobile nanoparticles might act as "plasticizer", improving orientation of the matrix. [20] This might induce the formation of a phase that is not accessible under normal conditions. For PP, the result lies in the appearance of b-crystal (see Supporting Information), in addition to the commonly occurring a phase.…”
mentioning
confidence: 99%
“…Consequently, the mobile nanoparticles might act as "plasticizer", improving orientation of the matrix. [20] This might induce the formation of a phase that is not accessible under normal conditions. For PP, the result lies in the appearance of b-crystal (see Supporting Information), in addition to the commonly occurring a phase.…”
mentioning
confidence: 99%
“…The authors also observed that such effect is not entirely due to the plasticizer chains, but there is a competition between the polymeric matrix and the plasticizer for the nanoparticle intercalation. In addition, Yalcin and Cakmak observed that there is a minimal concentration of each plasticizer, below which there's no ability to transmit the forces that reduce the particle size of the agglomerations. Correlating the FESEM images to TEM, it is possible to observe that the nanocomposites with the most regions of graphene agglomerates [Figure (c,f)] were the samples with the fewer regions with a second phase [Figure (c,f)], indicating that agglomerates alone can hinder the plasticizer molecules' movement.…”
Section: Resultsmentioning
confidence: 99%
“…[ 33 ] They exhibit the same refractive index, 1.57, in all directions within the basal plane (001). [ 33 ] They exhibit the same refractive index, 1.57, in all directions within the basal plane (001).…”
Section: Real Time Electric-birefringence Measurementmentioning
confidence: 99%
“…Layered clay platelets with their high aspect ratio enhance gas barrier properties in nanocomposites, [ 28 ] particularly when they are oriented with their broad surfaces in the plane normal to the diffusion direction. This orientation is easy to achieve by traditional fl ow processes such as extrusion, [29][30][31] fi lm blowing, [ 32 ] and fi lm stretching including uniaxial [ 33 ] and biaxial [ 34 ] stretching.…”
Section: Introductionmentioning
confidence: 99%